La población pobre en el Perú y el acceso a los servicios básicos periodo 2019-2023 - Mafaldo Vergara, Gina Evelyn (2025)
The crisis caused by the COVID 2019 pandemic in 2020 has had a negative impact on the fight against poverty in Peru, causing it to increase by almost 10 percentage points in that period. However, we cannot return to pre pandemic levels. The objective of this master thesis is to analyze the situation of the poor population in Peru in relation to access to basic services, in the period 2019 - 2023; For this purpose, this Quantitative – Descriptive research was carried out, with a Non-Experimental design. It is concluded that the population living in poverty in Peru during the five-year period 2019 - 2023 mainly accesses drinking water through the Public Network inside the Housing, since 75.94% of the population did so, a percentage that represents 6,687,933.00 people. Similarly, the analysis of the way to eliminate excreta from poor homes shows that 50.30% of the residents do so using the Public Network inside the Housing, meaning 4,429,942.00 residents. As can be seen, the coverage of this basic service only reaches 50% of the poor population, leaving the other half on the sidelines, evidencing the existence of a large gap to close. The next most used way is through a Septic Well, used by 14.07% of the population. The most used type of public lighting is Electric Power Through the Public Network, with a coverage of 91.07%, equal to 8,020,301 people.